The viscosity of liquid R134a - Oliveira, Carla Padrel de (2011)
The paper reports new measurements of the viscosity of liquid R134a over the temperature range 235 to 343 K and pressures up to 50MPa. The measurements have been carried out in a vibrating-wire viscometer calibrated with respect to the viscosity of several liquid hydrocarbons. It is estimated that the uncertainty in the viscosity data reported is +0.6%. The data therefore have a lower uncertainty than that of earlier measurements of the viscosity of this environmentally acceptable regrigerant. The viscosity data have been represented as a function of density by means of a formulation based upon the rigid, hard-sphere theory of dense fluids with a maximum deviation of _+0.3%. This representation allows the present body of experimental data to be extended to regions of thermodynamic state not covered by the measurements.